SOSIALISASI APLIKASI KEUANGAN UNTUK MENINGKATKAN KINERJA UMKM WARUNG AYAM PENYET BERKAH - Rahmawaty Hasibuan; Martalina Situmorang; Chris Dayanti Br. Ginting (COVIT (Community Service of Health), 2022)
Against the background of the awareness that financial records really need to be done to advance business, we are conducting socialization activities for one of the accounting recording applications, namely the "Accounting My" application which can be accessed on smartphones. The training was conducted at Warung Ayam Penyet Berkah with activities from introducing the application to using the application so that the application can be put to good use. The result of this activity is that the UMKM Warung Ayam Penyet Blessing is able to apply financial records using a smartphone application so that it helps the recording process which was originally using a manual system to become smartphone-based. Seeing current technological developments, it is hoped that all businesses can start carrying out accounting records using technology to make work easier. Keywords: Socialization, MSMEs, Financial Applications, Smartphone